Gender and Social Support for Sports among Vocational Schools Studets in Indonesia - Syah, Nur Rahmad; Rosidi, Sakban; Lani, Ahmad; Sucipto, Adi; Sunuyeko, Nurcholis (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
With the jargon